The Effectiveness of Hypnopressur Hegu Point (li4) and San Yin Jiao (sp 6) on the Duration of Labor in The First Stage of The Active Phase of Primigravida - Yeni Fitrianingsih; Noor Pramono Noor Pramono; Dw Pudjonarko; Hanung Prasetya (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Prolonged labor is a complication that increases maternal and fetal mortality. Hypnopressur is a therapy that is being developed to treat pain and length of labor. The aim of this study was to prove that hypnopressur is more effective in shortening the duration of active phase I primigravida labor. The study design was randomized control trial. The research subjects were 80 divided into 4 groups: hypnopressure group (HP) n=20, hypnotherapy (HA) n=20, acupressure (AK) n=20 and control group (K) n=20 Intervention in the active phase of the first stage of labor. Statistical test using Wilcoxon, Kruskal Wallis, and Treatment Effect Analysis Test (RR, RRR, ARR). Hypnopressur (HA) was effective in shortening the length of labor compared to hypnoaudio, acupressure and deep breathing supported by the median value of labor duration in the HP group of (120). The 4 groups showed a significant difference (p=0,032). The results showed that the test difference between the 2 treatment groups were as follows, the HP VS HA group had a difference but not significant (p=0,171), the HP VS AK group had a significant difference (p=0,031), there was a significant difference in the HP VS K group (p=0,006). HP was compared to the control group with an RR of 2,5 (CI 1,739 -28,174), meaning that the RR number was statistically significant and had 2,5 times shorter labor duration than the control group. ARR of 45% means that the difference in the ability of HP treatment in shortening the length of labor is 45% compared to the control group. Conclusion HP is more effective in shortening the duration of the first stage of labor in the active phase of primigravida.